2017
DOI: 10.1002/met.1610
|View full text |Cite
|
Sign up to set email alerts
|

Modelling maximum daily yearly rainfall in northern Algeria using generalized extreme value distributions from 1936 to 2009

Abstract: ABSTRACT:The generalized extreme value distribution is generally used to model annual maximum daily precipitation, and it then allows the calculation of the return values of this phenomenon. The distribution was fitted for selected stations in the north of Algeria; it was found that the generalized extreme value distribution of type I or the Gumbel distribution is more suitable for the Algiers and Miliana stations and the Fréchet distribution is more appropriate for the Oran station. The parameters were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Based on a sufficiently long observation series of the maximum annual daily precipitation, it is possible to predict P maxp% by using probability distributions of random variables. In hydrological studies, P maxp% is commonly determined by using the following probability distribution functions: normal distribution, log-normal distribution, Pearson's type III, exponential function, Gumbel's distribution, generalized extreme value distribution (GEV), and Weibull's and Pareto's distributions [7][8][9][10][11][12][13]. Wdowikowski et al [14] recommend the generalized exponential distribution for such a purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a sufficiently long observation series of the maximum annual daily precipitation, it is possible to predict P maxp% by using probability distributions of random variables. In hydrological studies, P maxp% is commonly determined by using the following probability distribution functions: normal distribution, log-normal distribution, Pearson's type III, exponential function, Gumbel's distribution, generalized extreme value distribution (GEV), and Weibull's and Pareto's distributions [7][8][9][10][11][12][13]. Wdowikowski et al [14] recommend the generalized exponential distribution for such a purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Seebocus et al 11 showed that the frequency distribution of rainfall data for Mauritius (see Figure 3) can be represented using the GEV distribution. In this study, the block maxima method is used with the GEV distribution, where the cumulative distribution function is formulated as 21 :…”
Section: Extreme Value Analysismentioning
confidence: 99%
“…Several other published papers have analysed extreme events in other areas using the GEVD, showing the importance of modelling extreme events and providing information such as return levels and periods as measures of extreme risk. [13] modelled annual maximum of daily rainfall in northern Algeria using the GEVD from 1936 to 2009 to estimate return levels at 2, 10, 20, 50 and 100 years return periods. Their results show an average of 100 years return period needed to record similar levels of 181.9mm of rainfall in Algiers, 173mm in Miliana and 109.54mm in Oran.…”
Section: Review Of Literaturementioning
confidence: 99%